Fostering Perseverance through Qur'anic Teachings: The Relevance of Grit in Islamic Education - Ubaidillah, Ubaidillah; Husni, Muhammad; Miranti, Miranti; Hatmiah, Hatmiah; Hulbat, Rahmad; Zubaidillah, Muh. Haris (LP. Ma'arif Janggan Magetan, 2024)
This study explores the concept of grit within the context of Islamic teachings, particularly the Qur’an, and examines its relevance to contemporary Islamic education. Grit, defined as perseverance and passion for long-term goals, is essential for overcoming obstacles in both academic and personal life. The purpose of this study is to investigate how Qur’anic principles such as sabr (patience), tawakkul (trust in Allah), istiqamah (steadfastness), and optimism can foster grit in students. Using a library research methodology, the study analyses key Qur’anic verses related to perseverance and connects them with the core elements of grit. The findings reveal that the Qur’an offers significant guidance on cultivating mental resilience, encouraging students to remain steadfast and hopeful in the face of challenges. Furthermore, the study highlights the practical application of these Qur’anic values in educational settings, suggesting that incorporating them into the curriculum can enhance character development and promote a growth mindset among students. In conclusion, this research demonstrates that by integrating the concept of grit from the Qur’an, Islamic education can better equip students to face both academic and life challenges with perseverance and determination, ultimately contributing to their success and well-being.